The Transformation of Islamic Education to Strengthen the Morals and Ethics of 21st Century Students - Hidayah, Tsabita Nawal; Kosasih, Aceng (Jurnal Pendidikan Nusantara, 2025)
This study aims to explore the influence of Islamic education on students' moral and ethical development using a qualitative literature review approach. It analyses findings from previous studies to understand how Islamic education contributes to character building based on the values of the Qur'an and Hadith. The results show that Islamic education not only serves as a means of knowledge transfer but also as a foundation for strong moral formation through the integration of values such as niyyah (intention), ikhlas (sincerity), and ihsan (excellence) in learning processes. Moral inculcation is further strengthened by family involvement, social environment, and a holistic curriculum. However, challenges include limited teacher competence, the negative impact of social media, and a lack of public awareness regarding the significance of Islamic education. This study proposes adaptive implementation strategies, such as improved teacher training, use of value-based digital media, and school-family collaboration. The novelty of this research lies in its critical synthesis of recent literature and its focus on linking Islamic educational principles with character formation in the face of globalisation. The findings offer significant implications for developing contextually relevant and value-oriented Islamic education policies and practices to nurture morally upright future generations.